Design and analysis of quasi-vertical multi-fin GaN power devices based on epitaxially grown GaN-on-sapphire - Jeong Woo Hong; Sang Ho Lee; Jin Park; Min Seok Kim; Seung Ji Bae; Won Suk Koh; Gang San Yun; In Man Kang (Journal of Science: Advanced Materials and Devices)
This study presents the design and analysis of a quasi-vertical multi-fin gallium nitride (GaN) power device based on GaN-on-sapphire epitaxy, simulated using three-dimensional technology computer-aided design. The proposed structure aims to overcome the limitations of lateral high-electron-mobility transistors for high-power applications, as well as to address the cost issues associated with fully vertical GaN structures. Device optimization began with a single-fin structure and progressed incrementally. First, we determined the optimal doping concentration for n-type GaN in the drift region and channel, followed by the application and analysis of the trench drain, source field plate, and multi-fin structures. The optimized device achieves impressive performance, with a specific on-resistance of 0.85 mΩ cm2, a breakdown voltage of 1263 V, and a Baliga's figure of merit of 1.87 GW cm−2. This study's systematic optimization and structural analysis provide valuable insights into enhancing device characteristics for high-power semiconductor applications and contribute to a deeper understanding of the electrical properties of quasi-vertical fin-type power devices.